KARAKTERISTIK BOBA OKRA MERAH DAN OKRA HIJAU DENGAN PENAMBAHAN PERBEDAAN TEPUNG SAGU DAN TEPUNG MAIZENA - Haryanto Adhiwono, Enrico Valent; Fitriyana, Vicha; Nur Laila, Eka; Muflihati, Iffah; Suhendriani, Sari (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2024)
Boba, or bubble tea pearls, is a popular food with a chewy texture produced from a mixture of starch and binders. This study aims to develop boba by utilizing red okra and green okra as additional ingredients, and explore the effect of adding sago starch and cornstarch in different proportions on the texture characteristics of the boba produced. This study used two types of okra, namely red okra and green okra, in the formulation of boba dough combined with sago flour and cornstarch with varying ratios: 80% sago flour and 20% cornstarch, and 90% sago flour and 10% cornstarch. Red okra produced boba with a distinctive reddish color, while green okra gave a brighter green color. Boba using 80% sago starch and 20% cornstarch showed a softer and chewier texture compared to boba using 90% sago starch and 10% cornstarch, which tended to be hard and stiffer. Mucilage from okra contributed to the increased chewiness, while the different proportions of sago starch and cornstarch affected the stiffness level of the boba.